Clean-Development Investments: An Incentive-Compatible CGE Modelling Framework - Böhringer, C; Rutherford, T; Springmann, M (Springer Netherlands, 2015)
Emissions offset schemes, such as the Clean Development Mechanism established under the Kyoto Protocol and sectoral crediting schemes which are currently discussed as a new market-based mechanism within the United Nations Framework Convention on Climate Change, allow industrialized Annex I countries to offset part of their domestic emissions by investing in emissions-reduction measures in developing non-Annex I countries. Here we present a novel modelling framework for offset schemes which can be used in computable general equilibrium models to quantify the sector-specific and macroeconomic impacts of clean-development investments. Compared to conventional approaches that mimic offset schemes as sectoral emissions trading, our framework adopts a micro-consistent representation of an offset scheme's incentive structure and its investment characteristics. In our empirical application, we show that incentive compatibility implies that the offset-generating sectors do not suffer, and that overall cost savings from the offset scheme tend to be lower than suggested by conventional modelling approaches. © 2014 Springer Science+Business Media Dordrecht.